Circadian leadership: A review and integration of chronobiology and leadership. (15th August 2022) - Volk, Stefan; Lowe, Kevin B.; Barnes, Christopher M.
Summary: A vast body of knowledge within the field of chronobiology highlights a broad array of important effects that circadian rhythms and chronotypes have on individual performance. Circadian rhythms are predictable fluctuations of energetic activation produced by an internal pacemaker, the circadian clock, that governs the daily functioning of the human body and mind. Chronotypes are individual differences in the setting of this biological clock that influence preferences for the optimal timing of daily periods of activity and rest. In this paper, we review the chronobiology literature as it applies to leadership research to advance a circadian leadership perspective that integrates circadian science with leadership science. We outline how a circadian perspective can help researchers to understand how time of day interacts with circadian processes to influence the effectiveness of task‐, relational‐, and change‐oriented leadership activities. Our circadian perspective also extends research on leader and follower individual differences by explaining the effects of chronotypes on leadership behaviors and outcomes. We develop propositions based on the most promising insights that have emerged from the literature review, advance ideas for future theory development and research, and discuss implications for leaders in practice.